2020
DOI: 10.1002/jsfa.10859
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of orange bagasse through one‐step physical and chemical combined processes to obtain a cellulose‐rich material

Abstract: BACKGROUND Orange bagasse (OB) is an agroindustrial residue of great economic importance that has been little explored for the extraction of cellulose. The present study aimed to investigate different combinations of chemical (sodium hydroxide, peracetic acid and alkaline peroxide) and physical (autoclaving and ultrasonication) treatments performed in one‐step processes for cellulose extraction from OB and to characterize the materials obtained according to their composition, morphology, crystallinity and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
2
3
0
2
Order By: Relevance
“…Mantovan et al [1] reported that cellulose content of OB processed by an isolated alkaline treatment increased from 12.4% to 54.7%, with a process yield of 25%, a value close to that observed in this study for the EXPNaOH sample (58.4%); however, in this study, the process yield was 35% (Table 1). The combined (physical and chemical) processes in one step are promising approaches to reducing environmental impacts and overall costs [2,38].…”
Section: Extraction Of Cellulose-based Materials With Extrusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mantovan et al [1] reported that cellulose content of OB processed by an isolated alkaline treatment increased from 12.4% to 54.7%, with a process yield of 25%, a value close to that observed in this study for the EXPNaOH sample (58.4%); however, in this study, the process yield was 35% (Table 1). The combined (physical and chemical) processes in one step are promising approaches to reducing environmental impacts and overall costs [2,38].…”
Section: Extraction Of Cellulose-based Materials With Extrusionmentioning
confidence: 99%
“…In general, each type of agro-industrial residue requires specific studies to optimize its use for cellulose production due to great variations in the chemical composition of agroindustrial residues, as well as preferably meeting the current demands for sustainable and competitive technological solutions. Conventional processes use a considerable amount of energy and an abundant number of reagents, including chlorinated agents, thus resulting in toxic effluents [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The use of lignocellulosic residues such as wheat straw, rice hulls, soybean hulls, orange bagasse, corn hulls, corn fiber, and oat hulls to obtain cellulose can be an interesting alternative to valorize these materials, which generally contain about 20-50% cellulose, 20-30% hemicellulose and 20-30% lignin, offering great opportunities for sustainable production integrated with biorefinery processes to obtain bio-based materials [1,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Bleaching pada isolasi selulosa dilakukan untuk meningkatkan derajat putih serat terdelignifikasi, menghilangkan komponen lignin, hemiselulosa, kromofor, abu, dan pektin yang tidak terdelignifikasi secara sempurna sehingga dihasilkan selulosa yang kemurniannya tinggi (Wildan, 2010). Agen bleaching yang umum digunakan pada proses isolasi selulosa, diantaranya asam perasetat atau PAA (Chattopadhyay et al, 2020;Mantovan et al, 2021;Zendrato, 2021), hidrogen peroksida (Sena et al, 2021), dan alkali hidrogen peroksida (Arnata et al, 2019). Penelitian ini menggunakan larutan PAA karena larutan ini memiliki bilangan oksidasi lebih tinggi dan kuat dibandingkan dengan hidrogen peroksida (Hidayati dan Zuidar, 2010), serta cenderung tidak merusak selulosa dan bebas klor sehingga lebih aman bagi lingkungan dibandingkan menggunakan senyawa klorin (Maharani, 2012;Sofian, 2011).…”
unclassified
“…Namun, waktu reaksi yang terlalu panjang dapat merusak rantai selulosa dan hemiselulosa pada serat. Penelitian Mantovan et al (2021) melaporkan bahwa proses bleaching selama 30 menit menggunakan larutan PAA pada ampas jeruk menghasilkan selulosa 56,1±1,5%, lignin 22,3±1%, dan indeks kristalinitas 39%. Penelitian lain yang dilakukan oleh Zendrato (2021) melaporkan bahwa proses bleaching menggunakan larutan PAA dengan waktu 60 menit pada batang kecombrang menghasilkan rendemen 47,8%, lignin 0,15%, holoselulosa 98,84%, dan α-selulosa 64,78%.…”
unclassified